As comemorações de um sesquicentenário em terras sul-rio-grandenses : os usos da memória da Revolução Farroupilha 1983-1985 - Ramos, Luciano Braga (2022)
This thesis aims to study the construction of memory proposed by the State Government of Rio Grande do Sul during the commemorations of the Sesquicentennial of the Farroupilha Revolution in 1985. For this, we will analyze the material found in the Historical Archive of Rio Grande do Sul (AHRS) in the Fund for the Sesquicentennial of the Farroupilha Revolution, as well as interviews carried out with people who participated at the time of the celebrations. This archive is composed of documents gathered by the event commissions from 1984 to 1986. Thus, I seek to understand the construction of memory by the subjects involved in the celebrations, such as the public and private sectors, as well as the institutions and intellectuals who joined to the proposal of the State Government; thus, also realizing the network of relationships built by the government that mobilized a large part of the society of Rio Grande do Sul around the Farroupilha celebrations; to analyze the subcommittees that brought together, on the one hand, historians from different institutions and trends, and on the other, traditionalists and folklorists with their peculiar way of representing the Farroupilha past. Thus, it will be possible to better understand how this memory was being rearticulated in the late twentieth century, and appropriated by the entities and individuals in question, giving meaning even today to the association of Farroupilha memory as a possibility of identification element for the South-Rio-Rio society grandense.